PENGARUH GAYA KEPEMIMPINAN TERHADAP LOYALITAS KARYAWAN DI STHALA, A TRIBUTE PORTFOLIO HOTEL - Sihombing, Irene Hanna H.; Martika, Made Uga; Sabudi, I Nyoman Sukana (Journal of Hotel Management, 2024)
Employee loyalty is a form of employee commitment to the company. To encourage employees to remain loyal to the company, it is essential to study the factors that influence employee loyalty. Leadership style plays a significant role in shaping employee loyalty. Generally, the better the leadership style, the more loyal employees will be in performing their activities within the company. This research aims to determine the influence of leadership style on employee loyalty at Sthala, a Tribute Portfolio Hotel. The sample size in this study is 70 respondents, using the saturated sampling method. Data was collected by distributing questionnaires using a 5-point Likert scale to measure 26 items. The data analysis techniques used include simple linear regression analysis, t-test, and the coefficient of determination, processed with SPSS version 23. The results of this study indicate that the Leadership Style variable (X) has a significant partial effect on Employee Loyalty (Y), with a t-value > t-table = 9.244 > 1.667 and a significance value < ? = 0.000 < 0.05. It can be concluded that the Leadership Style (X) has a positive and significant effect on Employee Loyalty (Y). The suggested recommendation is for the leaders at Sthala, a Tribute Portfolio Hotel, Ubud Bali, to continually provide motivation and guidance to help subordinates achieve the expected performance standards and to give fair rewards.